The satisfaction of long-stay senior tourists on tourism management in Cha-Am district, Petchaburi and Hua-Hin district, Prachuap Khiri Khan - Dr. Supattra Pranee; Dr.Tanapol Kortana; Panvipa Piyamputra; Dr. Monchai Rungthongpongampai (African Journal of Hospitality, Tourism and Leisure, 2019)
The purpose of this research is to study the factors influencing senior tourists’ decision making to take long-stay trips in Cha-Am and Hua-Hin Districts and also their satisfaction on tourism management in both districts. The population used for this study was a group of 400 long-stay senior tourists visiting both ChaAm and Hua-Hin. A quota sampling technique was used and data evaluation was processed by a statistical computer program (SPSS) for analysis of various statistical values consisting of number, percentage, average, standard deviation and analysis of variance. The study findings revealed that: 1) among those 400 senior tourists, most of them were males aged between 51-60 years old with a bachelor’s degree, selfemployed occupation and they were married, 2) at each different group of ages, their long stay satisfaction in Cha-Am and Hua-Hin Districts in view of tourism sport activities, health facilities and SPA service activity were different at least for 1 couple at statistical significance of .05, 3) with the different education level, the overall satisfaction on tourism sport activities: golf activity, fitness and SPA service activity appeared not to be different, 4) with respect to different types of occupation, the overall satisfaction on tourism sport activities, golf activity, fitness and SPA service activity appeared not to differ either, and 5) in terms of different marital status, the overall satisfaction on tourism sport activities, golf activity, fitness and SPA service activity also appeared not to be unlike.